164. Avoiding Complacency: Assessing the Perceived Impact and Value of Antimicrobial Stewardship at a Academic Medical Center - Lee, Matthew S (Open Forum Infect Dis, 2020)
BACKGROUND: Multi-disciplinary engagement and education remain key measures for Antimicrobial Stewardship Programs (ASPs). Over 3 years, our ASP has undergone key changes to pre-authorization review, post-prescriptive activities, and core team members, coinciding with a 30% increase in stewardship interventions. The objectives of this study were to evaluate the familiarity of Nursing, Pharmacy and Prescribers at our academic medical center regarding ASP activities and services, as well as perceived impact on patient care and value. Secondary objectives were to determine what resources are currently utilized and areas for improvement. METHODS: Distinct surveys were distributed to three participant groups: Nurses, Pharmacists, and Prescribers (Housestaff, Advanced Practice Providers, and staff physicians). Questions were developed to assess familiarity, perceived value, and overall satisfaction with the ASP. Additional items included questions on the current use of ASP resources and educational engagement. Survey results were compared to a similar survey conducted 3 years amongst the same participant groups. RESULTS: The survey was delivered electronically to 3367 Prescribers, Nurses and Pharmacists. 403 responders completed the survey (208 Nurses, 181 Prescribers, and 18 Pharmacists). Familiarity was lowest amongst Nurses, but almost doubled compared to 2016 (Figure). Prescribers cited “restricted antibiotic approval”, “de-escalation”, and “alternative therapies relative to allergies” as the three most common interaction types, similar to 2016. ASP interactions continued to be rated “moderate” or “high” value (88.4% vs 89.15% in 2016), however, face-to-face interactions were preferred by only 4% of responders (unchanged compared to 2016). Prescribers also responded uncommon use of ASP online resources (20%) and clinical decision support tools (34%). 78% of responders expressed desire for increased ASP-related education. [Image: see text] CONCLUSION: As ASPs evolve, it is important to constantly evaluate impact and value, and identify areas for growth. Despite ASP familiarity being high and interactions valued, we need to further optimize ASP provided resources, clinical support tools, and educational offerings. DISCLOSURES: All Authors: No reported disclosures